Design of a Miniaturized Electron Cyclotron Resonance Ion Source for High-Voltage Proton Accelerator - Hua-Fei Yu; Zi-Feng He; Ming-Hua Zhao; Wei-Shi Wan; Huan-Ling Liu; Yue Wu; Wen-Zhuang Lv; Da-Yong Zhou; Huan-Ting Lu (Applied Sciences, 2023)
The Electron Cyclotron Resonance (ECR) ion source fulfills high-current, high-efficiency, and compactness requirements for high-voltage proton accelerators. It is a cathode-free source that uses microwaves to heat a magnetically confined plasma, so there is no cathode loss resulting in a short service life. We finished the design for a miniaturization ECR ion source system, including a microwave system and source body. The traditional microwave system’s scale, which is approximately 1 m, has been reduced to 0.234 m, and the transmission efficiency is greater than 90%. The influence of cavity size and magnetic field distribution on gas ionization is analyzed under the condition that the outer size of the permanent magnet ring is limited, and the optimal scheme of cavity size and saddle-shaped magnetic field distribution is obtained. This design meets the requirement of fitting the ion source system into the restricted space in the high-voltage accelerator’s head.